Analisis Status Pekerja Freelance dalam Perjanjian Kerja Waktu Tertentu (PKWT) dalam Perspektif Hukum Ketenagakerjaan di Indonesia - Dalimunthe, Nikmah; Fajri, Muhammad Aulia (AHKAM, 2023)
Analysis of the status of freelancers in the Specific Time Work Agreement (PKWT) in the perspective of labor law in Indonesia is a study that aims to understand the relevant legal protections and employment arrangements for freelancers in Indonesia. Freelancers have grown rapidly in recent years, but their legal status and protection in the context of the employment relationship is still a concern. This study uses a qualitative research method that describes data using a series of sentences. The method used in this research is descriptive method. The descriptive method is a method whose data sources are words, pictures, and data from books, journals and other scientific works. In addition, everything collected has the potential to become a key to the Analysis of the status of Freelance workers in Specific Time Work Agreements (PKWT). The results of this study are that PKWT can be used to regulate the employment relationship between freelancers and employer companies. The PKWT must contain information regarding the type of work, the deadline for implementation, and the imbalances received by casual workers. Although casual workers do not receive the same protection as regular workers, they still have rights guaranteed by labor law, such as the right to an appropriate balance, reasonable working hours, and occupational health and safety protection.